User-Centred Design and Development of an Intelligent Light Switch for Sensor Systems - Boštjan Seničar; Helena Gabrijelčič Tomc (Tehnički Vjesnik, 2019)
The aim of the research was the user-centred design of an intelligent light switch with a focus on the definition of the natural and intuitive gestures for its manipulation, and to develop a multi-touch user interface and smart touch-based light switch that could be integrated into existing home environments and electrical wiring, with or without an existing intelligent system. After usability testing a prototype of the switch was constructed. The touch-panel, as the main interface, gave the users the ability to control one or more individual lights or light groups. The intuitive touch gestures for controlling the lighting were acquired with paper prototypes that were used for testing, and then integrated in the physical prototype. The results show that user-centred design is a valuable method for creating an intelligent touch-based light switch with a good user experience design, with or without a multi-touch user interface, and thus an approach that should be implemented in the development of a smart product.